SECURE AND HIGH-SPEED CRYPTOGRAPHY ARCHITECTURAL DESIGN TECHNIQUES FOR INTERNET OF THINGS - Krishnakumar, N J; Saravanan, N (The journal of contemporary issues in business and government, 2021)
Providing protection for the exchanged statistics performs a key role inside the modern-day world unsecured contact among IoT devices. As the technology develop giant portions of information are being exchanged, call for secure standards of encryption is as a result increasing. Security is more desirable so that in the center of the facts attack with the aid of intruders it isn’t always possible for the guys to be inside the conversation link. The protection method was carried out the use of the principle of symmetric, asymmetric, and hash algorithms. Elliptic Curve Cryptography is accomplished to encrypt and share the secret AES key among sender and receiver, As well because the Sophisticated Encryption Method for the encryption / decryption of the receiving data. In this paper, especially green architectures are carried out to ensure statistics conversation among users in the IoT perceptual layer via related to initialization, authentication technique and key generation, other than encryption. Sender combines facts encryption and key encryption earlier than it is despatched to the receiver with signature schemes. The receiver verifies the signature and decryption of the key applied to realize original statistics transmitted among the Perceptual Layer devices within the Internet of Things.